The evolution of the Indian nuclear power programme. (November 2017) - Banerjee, Srikumar; Gupta, H.P.
Abstract: The strategy for growth of nuclear power in India was planned nearly sixty years ago, noting the rather small uranium and large thorium reserves in the country. This has prompted India to adopt the well-known three stage programme. The first stage is primarily based on the Pressurised Heavy Water Reactors (PHWRs). The evolution of technology of PHWRs is discussed in the first part of this paper. India has constructed eighteen PHWRs, has achieved impressive availability factors and some of these reactors have achieved annual capacity factors of nearly hundred percent in the recent past. Having installed a nuclear power generation capacity of 6780 MWe (4460 MWe from PHWRs, 2000 MWe from PWRs and 320 MWe from BWRs), India is now poised to launch a major expansion programme. This will be based on the increased availability of uranium from import and from the augmented domestic supply. In the immediate future, the nuclear power capacity will grow by installing a series of indigenous PHWRs in addition to light water reactors built under international civil nuclear cooperation agreements. The growth of nuclear capacity in this period is aimed at increasing the share of nuclear power in meeting the base-load demand of non-carbon electricity required for the rapid economic growth in the country. India embarked on its second stage programme with the successful operation of a research reactor named Fast Breeder Test Reactor (FBTR). Based on the experience of FBTR and following the development of all the required enabling technologies in India, the Prototype Fast Breeder Reactor (PFBR) of 500 MWe (gross) capacity has been designed, constructed and is now at an advanced stage of commissioning. A large increase in the nuclear power generation capacity is envisaged through deployment of fast breeder reactors. These reactors will not only help in building up nuclear power capacity but also, in due course, enable conversion of thorium into fissile U 233, which will fuel the reactors in the third stage of India's nuclear programme. The adoption of the closed fuel cycle for both thermal and fast reactors has dual objectives: multiplying the fissile inventory by fertile to fissile conversion and reducing the burden of long lived radioactive waste-both being essential for attaining near sustainability of nuclear power. India has designed an Advanced Heavy Water Reactor (AHWR). This reactor can use one of the following fuels: (i) Low enriched uranium dioxide-thorium dioxide based mixed oxide (MOX) fuel primarily in once through mode. (ii) Plutonium dioxide – thorium dioxide MOX fuel in the closed fuel cycle mode. Eventually when enough of U 233 is generated the reactor can operate with the U 233 – thorium MOX fuel. A large number of passive safety features are incorporated in this design. As a part of the long term objective of the development of Accelerator Driven Sub-critical Systems (ADSS), work on the development of high power linear accelerator has been initiated. Highlights: Setting up of R&D facilities and planning the three stage nuclear power programme. Indigenisation of the PHWR technology, self sufficiency in production of fuels and heavy water. Development of fast breeder reactors and adoption of closed fuel cycle. Thorium utilisation including development of Advanced Heavy Water Reactor (AHWR). Evolving fuel cycle and R&D on accelerator driven subcritical systems.